The relationship between early childhood professional development, quality of care, and children's developmental outcomes - Madigan, Dara Michelle (Kansas State University, 2014)
An increased focus on school readiness in recent years has placed more attention on the importance of quality early care and education settings for children ages 3 to 5 years. The first five years of a child’s life represent a crucial period for development, and care settings impact children’s outcomes in a variety of domains. Preparation of teachers in order to provide a high-quality level of care that supports positive outcomes for children is critical. This report assesses the current state of the literature on effective professional development for early childhood professionals (primarily those working center-based settings with children ages 3 to 5 years), specifically as it relates to improved outcomes for children in the areas of social-emotional competence and language and literacy development. Methods for adult learning are also reviewed and recommendations for appropriate models of professional development based upon this review are provided. It is recommended that specific aspects within models of professional development be reviewed further to determine more concrete predictors in terms of what is effective for adult learning and application of concepts. It also is recommended that early care and education providers take part in professional development activities that have an added level of support and feedback, such as coaching, to assist in improving instructional practices to impact developmental outcomes in targeted areas, such as literacy.
Keywords: Early childhood education; Child care; Professional development; Child development; Child care quality; Early Childhood Education (0518)